The “society of knowledge” and education for everyone today La “sociedad del conocimiento” y la educación para todos, hoy - Pablo Gonzáles Casanova (Estudos de Sociologia, 2010)
The existence of a new “society of knowledge” with investigation, communication and propagation techniques is indubitable. However, in view of practices of knowledge privatization and nationalization of knowledge by the dominant class in the present exploitation model, and in a context of poverty and environmental destruction, politics that allow an institutional framework for the development of science and technology with public support and investment are necessary; politics that rescue classical theories, enriching them with new teachinglearning techniques and methodologies. Also, it is necessary to observe and reobserve, from a critical standpoint, the different sciences and the humanities, in order to generate alternatives for the construction of “another possible world”. Keywords: Society of knowledge. Investigation. Education. Propagation. Multiinter- trans-discipline. Alternatives. Es indudable la existencia de una nueva “sociedad del conocimiento”, con técnicas de investigación, comunicación y difusión. Pero, frente a prácticas de privatización del conocimiento y de nacionalización de saberes por parte de la clase dominante en el modelo actual de explotación, dentro de un contexto de pobreza y destrucción ambiental, se hacen necesarias políticas que otorguen un marco institucional al desarrollo de la ciencia y la tecnología con apoyo e inversión pública; que busquen la recuperación de las teorías clásicas, enriqueciéndolas con las nuevas técnicas y metodologías de enseñanza-aprendizaje. Asimismo, se hace necesario observar y re-observar a partir de un pensamiento crítico, las diferentes ciencias y humanidades, generando alternativas para la construcción de “otro mundo posible”. Palabras clave: Sociedad del conocimiento. Investigación. Educación. Difusión. Multi-inter-transdisciplina. Alternativas.